1988
DOI: 10.1111/j.1600-0609.1988.tb00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene probe analysis demonstrates independent clonal evolution of co‐existent chronic myeloid and chronic lymphocytic leukaemia

Abstract: We describe a case of Philadelphia‐positive chronic myeloid leukaemia occurring simultaneously with B‐cell chronic lymphocytic leukaemia in a 69‐yr‐old male. Gene probe analysis of DNA from both peripheral blood and bone marrow provided evidence for the independent evolution of 2 clones in this case, with a predominant population showing immunoglobulin heavy chain gene rearrangement and a smaller population showing a rearrangement within the breakpoint cluster region of chromosome 22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…To our knowledge, the series described in the present retrospective multicentre study is the largest so far reported in the literature: a total of 46 patients affected by CLL/MBL and concomitant MPN, followed by 15 Italian GIMEMA centers were analyzed in this study. In comparison with data emerging from the cases reported in the literature, we observed a lower incidence of CML (19.5% vs. 46.6%) [7–30] and PV (21.7% vs. 32%) [34, 35, 40–53], and a higher incidence of ET (39.2% vs. 21.4%) [31–39] and PMF (13% vs. 1.7%) [54]. In addition, we detected for the first time 3 cases (6.6%) of CLL associated with atypical CML (MPN/MDS).…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…To our knowledge, the series described in the present retrospective multicentre study is the largest so far reported in the literature: a total of 46 patients affected by CLL/MBL and concomitant MPN, followed by 15 Italian GIMEMA centers were analyzed in this study. In comparison with data emerging from the cases reported in the literature, we observed a lower incidence of CML (19.5% vs. 46.6%) [7–30] and PV (21.7% vs. 32%) [34, 35, 40–53], and a higher incidence of ET (39.2% vs. 21.4%) [31–39] and PMF (13% vs. 1.7%) [54]. In addition, we detected for the first time 3 cases (6.6%) of CLL associated with atypical CML (MPN/MDS).…”
Section: Discussionsupporting
confidence: 54%
“…The spectrum of secondary solid neoplasms during the course of CLL includes carcinomas of the skin, stomach, colon, breast, or kidney [4, 5]; among secondary hematologic malignancies, cases of acute lymphocytic, myelocytic, monocytic and myelomonocytic leukemia, erythroleukemia, plasma cell leukaemia [6], and myeloproliferative neoplasms (MPN) have been reported [7–54].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations